Implementation of Dakon Game in Stimulating the Development of Numeracy Literacy in Children Aged 5-6 Years at RA At-Thohiriyah - Qurrotul Uyun; Siti Farida; Dewi Pusparini (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to explore how the traditional game dakon can support the development of numeracy literacy in children aged 5–6 years at RA At-Thohiriyah. Numeracy literacy refers to the ability to understand numbers, count, and think logically in simple ways—skills that should be developed from an early age. The research used a descriptive qualitative method with observation, interviews, and documentation. The subjects were children aged 5–6 years. Initially, only a few children showed progress in numeracy. After using dakon with various number and pattern-related activities, more children showed improvement. The results show that dakon is a fun and engaging tool to stimulate numeracy skills. It encourages children to be more active and interested in learning because it matches their developmental stage. The use of dakon effectively improves young children's numeracy literacy and can be an enjoyable alternative learning tool.